Implications Of Intervention Of Kids' Athletics Practice Using Cooperative Learning Strategy By Competitive Style In Primary School - Bensikaddour , Habib; Ahmed benklaouz , Touati; Boumesjed , abdelkader; Esselma , Nouria (Journal of Sport Science Technology and Physical Activities, 2020)
Physical education is an important part of the primary curriculum and provides unique challenges for students involved in teaching.in this regard , Quality physical education in primary school optimises children’s well-being.In addition, Teachers should structure competitive activities to maximize the participation of all students.From this perspective , the teacher must model the desired outcome in the same way he demonstrates the critical elements of a kids' athletics .The aim of this experimental study is to determine the effect of the practice of the cooperation strategy by competitive style with a new concept that is the Kids' Athletics and their contribution to the improvement of teaching conditions in lesson of Physical Education and Sports in primary School, and the improvement of sports performance among students of the primary School in the long jump(m), shot put(m) , sprint 50 m (s) and endurance racing 1000 m (s) .for the very best practices that promote a higher level of participation among all students in physical education. This last is designed to give children the pleasure of playing athletics, to discover the sprinting, endurance running, jumping, throwing. Two groups of girls aged (10± 0.45 years) are participated. The experimental and control group each one of them (n=15).The results and according to the research variables characterized by significant differences (*p≤0.05).In this regard, the research team concluded that the use of the cooperative learning by competitive style in physical education will encourage a higher level of participation among many students in the activities of the kids' athletics that improve the physical performance of students and their relationships better than traditional teaching